The Impact of Responsive Parenting Program Towards Early Childhood Development Outcomes - Siti Aisah; Granasti Aprilia (SEAMEO CECCEP, 2023)
Apart from food, sanitation and access to health services, warmth and responsiveness by adult caregivers to a child’s needs are equally important for optimal survival and development. This research was carried out to examine the effect of a responsive parenting program towards early childhood development in 17 ChildFund-assisted locations in Indonesia. A comparative research design was used to compare results of responsive parenting implemented in both intervention and non-intervention groups. Quantitative data were collected out of interviews and assessments with parents and children, examining parenting knowledge, attitude, and practices among a total of 321 parents who participated in the program and 358 non-intervention parents. The development of a total of 311 children of the intervention group and 344 children of the non-intervention group were also measured. The main outcome of early childhood development towards 0 to 35-month-old children is measured through CREDI (Caregiver Reported Early Childhood Development Instrument) and IDELA (The International Development and Early Learning Assessment) for children aged 42 to 72-month-old. Changes in parenting behavior were measured using HOME (Home Observation for Measurement of the Environment) to disclose parental responsiveness and Multiple Indicator Cluster Survey (MICS) version 6 to observe the application of stimulation activities and parental discipline practices towards children.